Preconception vs. cognizance: The perception of DLSU BSA undergraduates towards the accounting profession before and during college education - Betita, Gennise Bernadette T. (Animo Repository, 2023)
Before entering college and selecting an accounting degree, students had already developed an impression of the profession. Subsequently, these students acquire first-hand exposure to courses connected to the profession during college. This gives an opportunity to study if time effectively influences the process of forming students’ perceptions of the accounting profession especially since it is a vital area of study, crucial for improving the profession’s image and better preparing students. Primary data from ID 121 Bachelor of Science in Accountancy students of De La Salle University – Manila, gathered through a survey questionnaire, was analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM), Paired T-Test, Wilcoxon Test, and Moderation Analysis. The statistical findings reveal that perceptions remained positively consistent before and during college. Before entering college, (1) Intrinsic perception was influenced by Ethical Attitude and Intrinsic Motivation, (2) Extrinsic perception was influenced by Ethical Attitude, (3) Prestige perception was influenced by Culture, and (4) Social perception was influenced by Ethical Attitude and Intrinsic Motivation. Meanwhile, ‘during college’ results revealed that (1) Intrinsic perception was influenced by Intrinsic Motivation, (2) Extrinsic perception was influenced by Ethical Attitude, (3) Prestige perception was influenced by Intrinsic Motivation, and (4) Social perception was influenced by Ethical Attitude. Additionally, only the students' social perceptions significantly differed before and during college. Overall, Time, as a moderating variable, had a buffering effect on the impact of Ethical Attitude on the Intrinsic perception of students towards the accounting profession.